Pixel Strength and Digitization of Radiographs - B Aarthi; M Jonathan Daniel; S V Srinivasan; Karthikshree V Prasad (Journal of Indian Academy of Oral Medicine and Radiology, 2007)
We performed a pilot study to compare the digitized images of panoramic radiographs with the original film images for perceived clarity and diagnostic quality, and to make comparison amongst the digitized film images captured by a digital camera at different resolution settings to assess if differences in clarity and/or diagnostic quality existed. Eight orthopantomograms were photographed using a digital camera, Nikon Finepix S7000, at four different resolution settings - 1 M pix, 3 M pix, 6M pix and 12 M pix respectively. These thirty two digital images were transferred to a laptop computer, Acer Travelmate 290 E, saved as JPEG files and viewed using ′Planmeca Dimaxis′ software. Five observers made comparison between the film and digitized images and also amongst the images digitized with various pixel strengths. Images were ranked for clarity and diagnostic quality. Data was analyzed using statistical tests. Results indicated no significant difference in clarity and diagnostic quality between conventional radiographs and their corresponding digitized images. The images digitized with the highest resolution were better than those digitized with the other lower resolutions.